Analisa Determinan Kejadian Kelahiran Prematur Di RSIA Rika Amelia Palembang - Nanik Zulaikha; Fika Minata (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Preterm birth is a birth that occurs at less than 37 weeks of gestation. At RSIA Rika Amelia, the incidence of preterm birth in 2017 was 82 people (13.6%), then in 2018 there was an increase of 136 people (16.03%) and in 2019 it increased to 213 mothers (20.4%). Objective: To determine the relationship between maternal age, parity, history of preterm birth, short distance between 2 pregnancies and the incidence of preterm birth. Methods: This study used an analytic survey method using a cross sectional approach. Population of 1011 mothers sneezing at RSIA Rika Amelia Palembang. Samples were taken by simple random sampling technique of 254 samples. Using univariate, bivariate and multivariate analysis with logistic regression methods. Results: The results of this research were univariate analysis of 254 respondents who experienced preterm labor as many as 105 respondents (41.3%) and as many as 149 people (58.7%). The results of bivariate analysis of the variables of maternal age (p = 0.001), parity (p = 0.002), history of preterm birth (p = 0.003), a short distance between 2 pregnancies (p = 0.001) showed a significant relationship with the incidence of preterm birth from The results of the analysis from the results of multivariate analysis, the most dominant factor in the incidence of preterm birth was the age of the mother with OR = 3.382: P-value = 0.000 (95% CI: 1.810 - 6.320). Conclusion: The most dominant factor in the incidence of preterm birt histh eage of themo ther